Threat simulation in NREM and REM sleep dreams across the night - Shintami, Samuli (fi=Turun yliopisto|en=University of Turku|, 2018)
This study is based on the threat simulation theory of dreaming (Revonsuo, 2000) according to which the nature of dreaming is threat simulation and the function of threat simulation is improved evolutionary adaptedness. Simulated threats enabled ancestral humans to practice threat perception and avoidance behaviors in the safe environment of sleep and provided a selective advantage by increasing survival rate. If threat simulation is the function of dreaming, threats should be frequently simulated in dreams, across the night and in all sleep stages. Threat content analyses conducted in earlier studies have utilized home dream diary reports which are mostly late morning dreams (e.g., Revonsuo & Valli, 2000; Valli et al., 2007, 2008). In this thesis, for the first time an analysis of the frequency and quality of threatening events in Non Rapid Eye Movement (NREM) and Rapid Eye Movement (REM) sleep dreams across the night was conducted, to investigate whether threats are equally frequent and qualitatively similar in all sleep stages, throughout the night. The dream data were collected by the Department of Psychiatry of Harvard Medical School in the 1990s from 16 undergraduate students, with the ‘Nightcap’ which enables pre-programmed awakenings, and tracking of sleep stages and time spent asleep in the setting of the participant’s own home. The dream sample utilized in this study consists 232 dreams produced by 15 participants. The dream reports were analyzed utilizing the Dream Threat Scale (Revonsuo & Valli, 2000). The results of this study show that threatening events are present in both NREM and REM sleep dreams and across the night. The frequency of threatening events was higher in REM than in NREM dreams and in late than in early dreams. However, these perceived differences vanished when the word count of dream reports was controlled for which suggests that the differences were mediated by report length. The quality of dream threats did not differ between sleep stages or across the night. Given that threatening events are present in NREM and REM sleep dreams across the night, and their nature is not affected by sleep stage or time of night, the prediction of the threat simulation theory that dreams are specialized in the simulation of threatening events gains support.